Balanghai International Incorporated a production systems study - Ballesteros, Patrick; Bayron, Eric L.; Delmo, Femelyn A.; Guerrero, Honorio Jerome; Ouano, Mary Grace (College of Engineering, 1993)
This paper is a production systems study of Balanghai International Incorporated, an export-oriented firm engaged in the manufacture of lampshades made from capiz and stained glass.. Based on the company's immediate needs, the study focused on the following areas: 1. Inventory management, 2. Capacity planning and 3. methods study of the firm's assembly operation. The company identified their inventory as a major problem area because of their current large stock of capiz and glass. They have, in stock, too many panels of glass of various colors which are not all being utilized, and thus a large portion of their capital is tied up. However, the company has no complete records of their inventory, nor of their materials usage which therefore posed a major limitation of for the team. Forecasts and inventory management techniques were applied to their existing records. For the analysis to be completely reliable and useful, the team has proposed simple means to get the company's record organized. The company was also quick to identify their assembly operation as an area which needs major improvements. According to management, all the other operations--cutting, binding etc--were already performing at Taiwan standards except for the assembly operation which results in a bottleneck situation. There were no time standards which prompted the group to conduct a time and methods study of the assembly operation. Line balancing played a major role in the successful creation and testing of a proposed system that can increase the company's daily production efficiency by at least 76%. However, the other production sections may not sufficiently supply the increased requirements of the assembly section. Also, the company's present work force do not have permanent tasks. Workers shift from one production section to another depending on the workload present. These tow major concerns prompted the study team to conduct a capacity planning analysis. THe group wanted to find the optimal arrangement or staffing of workers per workstation that could satisfy the requirements of assembly, create permanent work assignments, and consequently create a basis for the production capacity of the entire plant. A modification of the present facility layout (production floor layout) to accommodate the expected increase in production flow was also made. Under the proposed layout, production flow become smoother and travel distances were reduced. Most of the benefits derived from the various recommendations were qualitative and were not directly or easily quantifiable. However, the proposal for the methods section entails a minimum monthly net benefit of P 80,000.00 for the company. Most of the costs involved in the proposals were negligible because the proposals refrained from any capital outlay and focused more on increased utilization of the current assets of the company. An Ishikawa diagram has been prepared in section 4.0 which shows how the study team interpreted and consequently tackled the current problem of the company.